Policy Model Corporate Social Responsibility during The Covid-19 Pandemic: (Empirical Finding of State Own Enterprises in North Sumatra Province, Indonesia) - Azizul Kholis; Lukitaningsih; Sulaiman Lubis (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to examine the company's Corporate Social Responsibility (CSR) fund management policy model, namely both internal factors and external factors. The test was carried out on State Owned Enterprise in North Sumatra Province, Indonesia during the Covid 19 pandemic so that it could be seen what CSR policies were taken by companies in helping the government funding with the Covid 19 pandemic in Indonesian. The sample are 48 state-owned enterprise in this province. The data collection technique is distributing questionnaires through google form, email and other social media. Based on stakeholder theory and corporate social responsibility concept, two variables that influence the company's CSR policies are tested, namely Internal factors with indicators of planning strategies and human corporate culture while External factors support government and public pressure. The novelty of this research is disaster contingency as part of variable Which have effect to CSR Policy. Its means disaster contingency can become important thing to support CSR policy. The results of hypothesis testing with multiple regression indicate that CSR policies are significantly influenced by both internal and external variables. The limitation of the study is that the sample is only one province with small amount of sample and is recommended for a wider research area. The implication of the research is that the government should issue regulations to regulate CSR activities, especially those oriented to handling Covid 19 so that CSR can be more useful.